2020
DOI: 10.2337/dc20-1380
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia at Hospital Admission Is Associated With Severity of the Prognosis in Patients Hospitalized for COVID-19: The Pisa COVID-19 Study

Abstract: To explore whether at-admission hyperglycemia is associated with worse outcomes in patients hospitalized for coronavirus disease 2019 (COVID-19). RESEARCH DESIGN AND METHODS Hospitalized COVID-19 patients (N 5 271) were subdivided based on at-admission glycemic status: 1) glucose levels <7.78 mmol/L (NG) (N 5 149 [55.0%]; median glucose 5.99 mmol/L [range 5.38-6.72]), 2) known diabetes mellitus (DM) (N 5 56 [20.7%]; 9.18 mmol/L [7.67-12.71]), and 3) no diabetes and glucose levels ‡7.78 mmol/L (HG) (N 5 66 [24.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
132
4
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 16 publications
19
132
4
10
Order By: Relevance
“…While Li et al [13] demonstrated an increase trend in all-cause mortality (HR 3.29; 95% CI, 0.65-16.6) in patients with hyperglycemia without diabetes (FPG 5.6-6.9 mmol/L and/or HbA1c 5.7-6.4%), compared to normoglycemic patients (FPG < 5.6 mmol/L and HbA1c < 5.7%) with COVID-19, at a mean follow-up of 30 days. The most recent study by Coppelli and colleagues reported that mortality was significantly higher in hyperglycemia without diabetes (defined as no diabetes and glucose 7.78 mmol/L at admission) compared with normoglycemic patients (at-admission blood glucose < 7.78 mmol/L) with COVID-19 (39.4% vs. 16.8% respectively; unadjusted HR 2.20; 95% CI, 1.27-3.81; p = 0.005) at a mean observation of 17 days period [14].…”
Section: 1mentioning
confidence: 97%
“…While Li et al [13] demonstrated an increase trend in all-cause mortality (HR 3.29; 95% CI, 0.65-16.6) in patients with hyperglycemia without diabetes (FPG 5.6-6.9 mmol/L and/or HbA1c 5.7-6.4%), compared to normoglycemic patients (FPG < 5.6 mmol/L and HbA1c < 5.7%) with COVID-19, at a mean follow-up of 30 days. The most recent study by Coppelli and colleagues reported that mortality was significantly higher in hyperglycemia without diabetes (defined as no diabetes and glucose 7.78 mmol/L at admission) compared with normoglycemic patients (at-admission blood glucose < 7.78 mmol/L) with COVID-19 (39.4% vs. 16.8% respectively; unadjusted HR 2.20; 95% CI, 1.27-3.81; p = 0.005) at a mean observation of 17 days period [14].…”
Section: 1mentioning
confidence: 97%
“…However, Cariou et al reported that the observed effect diminished following adjustments for clinical and biological features (odds ratio 1.30 [95% CI: 0.94-1.82]), 25 while Coppelli et al stated otherwise, 31 Moreover, exposure-response trend were also observed in two studies, 31,42 Appendix Table S10). 31 However, we were unable to perform a formal dose-response analysis due to insufficient information. In addition, two studies also reported that the risk of mortality was more accentuated in patients without history of diabetes 30,31 31 Subgroup and sensitivity analyses, as well as publication bias assessment and DRMA was not conducted due to insufficient number of studies.…”
Section: Random Blood Glucosementioning
confidence: 99%
“…From 35 included studies, more than half were conducted in China (23 studies), while the others were five each in America 18,21,[27][28][29] and Europe 20,25,[30][31][32] , and one each in Hong Kong 33 and South Korea 34 . FBG was utilized in 23 studies, while RBG in 13 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations